Teacher professional learning communities and children’s school readiness in China: the moderating role of supportive conditions and cooperative atmosphere - Ren, Jie; Mo, Yunjuan; Zhang, Yulong; Hou, Yuna (Frontiers in Education, 2025)
IntroductionThis study examined whether teacher professional learning communities (PLCs) established through a collaborative effort between kindergarten and primary school teachers can effectively promote Chinese children’s school readiness and explore the policy conditions that stimulate such a facilitative effect.MethodsA total of 839 children and 67 teachers in kindergartens from Chongqing, China, participated in this study. Firstly, we used descriptive statistical analysis to determine the overall situation of teacher PLCs. Subsequently, a series of mean difference tests and multiple linear regression analysis were used to test the relationship between teacher PLCs and children’s school readniess.ResultsThe results indicated that the three dimensions of teacher PLCs, including shared vision, collaborative practice, and resource sharing, significantly and positively predicted children’s school readiness. Chinese teachers scored highest in the dimension of shared vision, followed by collaborative practice, and lowest in resource sharing. The collaborative atmosphere of teacher PLCs enhanced their effects on children’s school readiness, while the supportive conditions of teacher PLCs were ineffective.DiscussionThe empirical findings from this study broaden the scope of existing research on teacher PLCs and provide information from a Chinese context about improving children’s early development to benefit international society.